Analisa Pengendalian Kualitas Produk Dengan Metode Six Sigma PT. XYZ - Ahmad, Saiful; Hakim, Cikita Berlian; Ridwan, Achmad; Firmansyah, Nunung Agus; Hana, Fida Maisa; Muadzah, Muadzah (Metode : Jurnal Teknik Industri, 2025)
PT XYZ. Is an industrial company that produces galvalume toilet doors. August 2024. Successfully produced 11,147 non-coloring galvalume doors and 1,645 existing defective products. These problems are caused by a variety of factors including machines, people, and materials. To overcome this problem, the Six Sigma method was integrated with the DMAIC approach. The aim of this approach is to identify the causes of defects and provide solutions and preventive measures to reduce the occurrence of defective products. Types with broken rivets 49.06%, fast frame coming off 19.88%, loose 11.00%, loose 5.11%, black scratches 2.86%, rivets not up to 2.55%, brand, rust & scratches 2.43%, brands & scratches 1.52%, length 1.46%, dents & loose 1.22%, stains & scratches 0.97%, tilted 0.36%, black stains 0.30%, poor installation 0.30%, loose & loose connections 0.30%, scratches & dents 0.18%, rusted 0.12%, rust & scratches 0.12%, dents 0.12%, loose connections 0.06%, reversed 0.06%. Broken rivets are the most common cause of product defects. PT. XYZ. Measured using defects per million occurrences (DPMO) and shows that the quality of the door product is at a sigma level of 6.030 and a DPMO value of 4.676. Factors include galvalume and rivet nails that do not meet production standards, as well as worker negligence during the production process. Based on these findings, several suggestions were put forward, including the need for a control list to check good and bad raw materials.